Reptiles and Amphibian Diversity, Along with Potential Treat in Sumber Nyolo, Malang Regency - Berry Fakhry Hanifa; Muhammad Asmuni Hasyim; Bayu Agung Prahardika; Nurul Whika Agustin (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2022)
Inventory of reptiles and amphibians was carried out in the Sumber Nyolo area, Karangploso District, Malang Regency, East Java. The sampling area is at an altitude of 600-650m above sea level. Pre-survey was conducted once. The survey was conducted from June-October 2020 using the visual encounter (VES) method. A total of 167 individuals from 17 species, 10 families have been recorded, 1 of which is in Near Threatened (NT) and Vulnerable (VU) status on the IUCN Redlist namely Ptyas korros and Huia masonii respectively, which H.masonii also endemic to Java Island. The diversity index (H’) shows a moderate value (2.099), while the dominance value (0,211) was lower than the evenness index (0.479). The species with the largest population was Chalchorona chalchonota (70 individuals), while Huia masonii, Ptyas korros Gekko gecko, and Xenochrophis sp. was the fewest species found (1 individual). Threats to this area include habitat destruction due to land conversion into tourism area and religious destination as well as rice fields in the downstream and settlement area